California - Benson, Sara; Bender, Andrew; Bing, Alison; Brash, Celeste; Ho, Tienlon; Kohn, Beth; Skolnick, Adam; Vlahides, John A. (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2015)
Presents a guide to California, describing accommodation, restaurants, transportation, shopping, major points of interest, and sightseeing activities.
At head of title: Lonely Planet.
"100% researched & updated, best planning advice, top sights in full details"--Cover.
Includes index.
Keywords: California -- Guidebooks; California -- Description and travel